Burkina Faso : Structural Adjustment Credit III - Mohan, P. C. (World Bank, Washington, DC, 2012)
The overall objective of the US$25 million credit, which closed in June 2000, was to support a reform program aiming at: a) enhancing the competitiveness of the Burkinabe economy to substantially raise growth rates over the medium term and alleviate poverty; b) improving public finance management, particularly with regard to tax policy and the use of public resources; and c) completing the third phase of the common external tariff (CET) adopted by the west African Economic and Monetary Union (WAMEU). This Note discusses the impact on the ground and the lessons learned from the project implementation.